A Study of the Philosophy of Science on Science, Knowledge, and Science in Elementary Education at SDN 3 Tlogosari Sumbermalang - Ima Nurmala Sari; Lilis; Sisca Prahasti Widianingrum K.; Tamsik Udin (Penerbit Hellow Pustaka, 2026)
The philosophy of science plays a fundamental role in providing a conceptual foundation for the development of knowledge, particularly within the field of basic education. This article aims to examine the concepts of science, knowledge, and scientific knowledge from the perspective of the philosophy of science and their implementation in basic education practices at SDN 3 Tlogosari Sumbermalang. This study employs a qualitative approach, utilizing literature review and descriptive observation methods. The results indicated that an understanding of the philosophy of science helped teachers distinguish between empirical knowledge and systematic scientific knowledge, thus rendering the learning process more critical, reflective, and meaningful. The integration of the philosophy of science into basic education is essential for fostering students' scientific mindsets from an early age.